2013
DOI: 10.11607/jomi.3057
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Radiographic Detection of Cement Overhangs on Cement-Retained Implant Restorations

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…If a provisional luting cement is to be used in the cementation of an implant abutment, the most radiopaque cement available should be used. Radiographic evaluation of the implant margins after abutment cementation has been recommended (41)(42)(43). Insufficient removal of cement excess could lead to periodontal and peri-implant problems.…”
Section: Dental Cementsmentioning
confidence: 99%
“…If a provisional luting cement is to be used in the cementation of an implant abutment, the most radiopaque cement available should be used. Radiographic evaluation of the implant margins after abutment cementation has been recommended (41)(42)(43). Insufficient removal of cement excess could lead to periodontal and peri-implant problems.…”
Section: Dental Cementsmentioning
confidence: 99%
“…Therefore, it is advantageous to use a radiopaque luting agent to aid in detection of excavated cement in the peri‐implant region, thereby reducing the incidence of cement‐induced peri‐implantitis . Excess cement around the implant restorations may be detected with high probability by digital radiographic procedures, and the minimum radiopacity value should be higher than that recommended by ISO directives, supporting the use of highly radiopaque cements . Variolink Implant is a special luting cement for use in implant dentistry, and the results from this study confirmed the high radiopacity, at almost 2.5 times greater than that of human enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Antonijevic et al showed that the radiopacities of SpeedCem and RelyX Unicem were 4.15 mm and 2.25 mm of aluminium thickness, respectively. They concluded that the minimum radiopacity value should be higher than that recommended by ISO, and clinicians should use highly radiopaque dental cements . In their previous study, the greatest radiopacity values of aluminium equivalent were demonstrated by Variolink II (5.12 mm), Multilink Automix (4.43 mm), and SpeedCem (4.15 mm) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations